Investigation of the Phase Composition of Lithium-Titanium Ferrites by Thermo-Magnetometric and X-Ray Analysis; Advanced Materials Research; Vol. 1085 : Prospects of Fundamental Sciences Development (PFSD-2014) - Astafyev A. L. Alexander Leonidovich (Chemistry and Physics of Materials, Environmental Materials, 2015)
Title screen